Studi Timbulan Dan Mass Balance Sampah Di Universitas Islam Negeri Sultan Syarif Kasim Riau - Dicky Maulana; Elvi Yenie; Gunadi Priyambada (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
All human activities human will produce a residual in a form of solid called solid waste. UIN SUSKA Riau campus is a one of university in Pekanbaru with all of its activities is not hampered from solid waste production and problems coming from it, the solid waste accumulation for long days is some of problem coming out from the lack of intergrated solid waste management. This study aims to determine the waste generation and composition at UIN SUSKA Riau campus and planned waste management system that includes storage, collection, transportation in UIN SUSKA Riau campus. This study begins with the generation and waste composition studies conducted in 3 faculty, 3 offices, and 4 supporting fasilities. The study results showed the composition and in 2019 the daily waste generation of 556,28 kg/day in mass unit and 5.785 l/day in volume unit with generation is anorganic waste by 26,47% % and organic waste by 73,53%. The mass balance of the weight of daily garbage with an average weight of 556.28 kg / day, the waste that can be utilized is 436,58 kg / day and the weight of the garbage dumped is 119.68 kg / day. The recommended recycling potential is composting of 74.95%, while recycling is 24.33%. Keywords: mass balance, UIN SUSKA Riau Campus, waste generation,